Evaluative Study of Learning Discrete Mathematics Using Mobile Learning (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Mobile learning has emerged as a transformative approach to education, offering flexibility and accessibility to learners across diverse disciplines. Discrete Mathematics, a fundamental subject in computer science and related fields, presents unique challenges due to its abstract concepts and logical reasoning requirements. This review paper observes the effectiveness of mobile learning tools in enhancing the understanding and engagement of students in Discrete Mathematics. By analyzing recent advancements in mobile learning applications, pedagogical strategies, and student performance metrics, this study evaluates the potential of mobile platforms to address common learning barriers. Key considerations include the integration of cooperating features such as gamification, quizzes, and real-time feedback, as well as their impact on critical thinking and problem-solving skills. The review also highpoints the role of accessibility, user experience, and adaptive learning in shaping outcomes. Findings suggest that mobile education offers significant advantages in improving comprehension and motivation, though challenges such as screen size limitations and the need for personalized content persist. This paper contributes to the growing body of research on mobile learning by providing insights into its applications in teaching complex mathematical concepts.